AUTOMATED OFFICE BLOOD PRESSURE (AOBP) IS LOWER THAN OFFICE BLOOD PRESSURE (OBP) BUT HOW IT COMPARES WITH AMBULATORY BLOOD PRESSURE MEASURES (ABPM)?. (June 2018) - Strocchi, E.; Mastini, M.; Rosticci, M.; Borghi, C.
Abstract : Objective: Due to blood pressure (BP) variability it is difficult to define the most representative BP values of each patient and the limits of OBP are well known; even though OBP remains the usual reference for medical decisions, ABPM is increasingly preferred because it may supply a more informative picture of BP load. A new method of BP measurement, that is AOBP, it has been proposed after the impressive results of the SPRINT study that, however, raised quite a bit of discussions. The aim of this study was to compare the AOBP with ABPM in an unselected sample of subjects. Design and method: Before starting the ABPM, AOBP was also measured on the same arm for 5 minutes after 10 minutes of rest in a quiet room with the patient alone. ABPM with less than 90% BP values were excluded; then the results of ABPM where analyzed taking into account the exact time the patient went to bed and raised as written on the diary. Therefore we calculated the daytime and nighttime BP mean and we also averaged the lower tertile of BP measurements that we called "basal" BP. 100 unselected subjects were considered for the analysis. Results: As expected systolic AOBP was on the average 15 mmHg lower than OBP and this was due to the presence of the physician and not to the measuring device. On average the AOPB was very similar to the "basal" BP but with wide variations in the individual patients. Conclusions: The variables associated with such a different behavior of AOBP are being investigated.